Economic Growth Viewed from Life Expectation Levels, Wholesale Trade, Business Trend, Consumer Trends and Received of Zakat, Infaq and Alms - Syahrul Hidayat, Muhammad; Eko Sujianto, Agus; Arif Faizin, Mochamad; Nurrohman, Dede; Mashudi, Mashudi (Journal of World Science, 2023)
This research aims to identify and analyze the effect of life expectancy, wholesale price index, business tendency index, and consumer tendency index on economic growth with zakat, infaq and almsgiving receipts as intervening variables in Indonesia. The method used in this study is a quantitative method with the type of associative research, population and sample in this study is Indonesia's Economic Growth Quarter I 2005 – Second Quarter of 2022 Central Statistics Agency. Based on research on life expectancy, the wholesale price index, the business tendency index, and the consumer tendency index have a significant positive effect on economic growth in Indonesia. The results of this study indicate that the receipt of zakat, infaq, and alms has a significant positive effect on Indonesia's economic growth. It can be concluded that it can contribute to the government, zakat managers, the general public, both academics and economic actors and the general public so that they understand more about the linkage of life expectancy, wholesale price index, business tendency index, consumer tendency index to economic growth.